1993
DOI: 10.1128/aac.37.4.652
|View full text |Cite
|
Sign up to set email alerts
|

Activities of fluoroquinolone, macrolide, and aminoglycoside drugs combined with inhibitors of glycosylation and fatty acid and peptide biosynthesis against Mycobacterium avium

Abstract: Smooth-and rough-colony variants of Mycobacterium avium serovar 4 were treated with three classes of drugs. The drugs were chosen for their potential inhibitory effects on the biosynthesis of the cell envelopeassociated serovar-specific glycopeptidolipid antigens. Growth was monitored radiometrically with a BACTEC 460-TB instrument, and MICs were determined for each drug. Both variants were then treated with inhibitory drugs in combination with antimicrobial agents that have demonstrated effectiveness against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 42 publications
(50 reference statements)
3
34
0
Order By: Relevance
“…The multidrug resistance of MAC is usually ascribed to intrinsic properties of the organism's lipid-rich cell wall, although additional factors may contribute (2,19,23,27,36). A role for the cell wall has been inferred from indirect observations.…”
mentioning
confidence: 99%
“…The multidrug resistance of MAC is usually ascribed to intrinsic properties of the organism's lipid-rich cell wall, although additional factors may contribute (2,19,23,27,36). A role for the cell wall has been inferred from indirect observations.…”
mentioning
confidence: 99%
“…When examined by TLC, the distribution of radioactivity in internally radiolabeled lipids extracted from MAC 702 revealed a group of lipids that radiolabeled with [14C]Phe and ['4C]Ile (Fig. 1) [7,91. The HPLC pattern for radiolabeled lipid extracted from MAC702 is given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Neither lipopeptide contained alaninol, a component commonly found in glycopeptidolipid components, and neither contained carbohydrate [lo]. The presence of the phenylalanineisoleucine-containing lipopeptide has been noted in three rough- colony variants of M. avium serovars 4, 8, and 20 [9], a smoothcolony variant of serovar 4 [7], and more recently has been observed in a smooth-opaque, a smooth-transparent, and roughcolony variant of at least one other M. avium isolate [31]. In addition, Belisle et al have reported the presence of a phenylalanine-containing lipopeptide proposed to be a precursor in glycopeptidolipid biosynthesis [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations